THE MICROFINANCE INSTITUTIONAL SUSTAINABILITY AND EMPOWERMENT OF WOMEN BORROWER’S IN MALAYSIA: AN EMPIRICAL REVIEW - Arshad, Ali; Bhuiyan, Abul Bashar; Kassim, Aza Azlina Md; Ali, Md Jafor; Saad, Muhammad (American International Journal of Multidisciplinary Scientific Research, 2021)
The fundamental aims of this study to construct a new framework between Microfinance Institution’s (MFIs) financial sustainability and social, economic and household women empowerment in Malaysia. The study used both quantitative and qualitative approach. The study used available online empirical recourses by the name of Microfinance Institution’s (MFIs) sustainability and sustainable and social, economic and household women empowerment in different online database sources such as Google Scholars, Springer Link, Wiley, Science Direct, JSTOR, Emerald full text, Scopus, and EBSCO HOST etc. The summary of literature review revealed that it is the unique goal of MFIs for poverty reduction mission through ensuring of financial sustainability while contribution impact in the society. It has also revealed that it is the way the social mission of poverty alleviation through serving the poorest has been overshadowed by profit motive. However, profit orientation of the microfinance industry also emphasis on profit earning. The present study will be recommended for policy considerations for the successful and effective operation of microfinance programs by providing the necessary guidelines for the proper utilization of loan for women borrowers in Malaysia.